LEGAL STUDY OF HUMAN TRAFFICKING JURISPRUDENCE IN THE MILLENNIAL ERA - Ayu Lestari, Tiara; Yulviani, Dian (International Journal of Business, Law, and Education, 2023)
The Millennial Era Human Trafficking Law Study investigates the definition of human trafficking in Article 3 of the United Nations Protocol to Prevent, Suppress, and Punish Trafficking in Persons, Especially Women and Children. It consists of three components: exploitative actions, means, and intent. By extending traffickers' connections and opportunities to recruit and exploit victims, globalization and technological progress facilitate the spread of human trafficking. There are 49.6 million people living in modern slavery, 27.6 million of whom are forced to work and 22 million of whom are compelled to marry. Human trafficking is a complex and multifaceted problem caused by poverty, injustice, conflict situations, gender discrimination, tolerance for violence against women and children, a lack of appropriate laws and political will, restrictive immigration policies, globalization of the sex industry, transnational engagement, and organized crime networks. Due to global threats, the study of human trafficking law in the twenty-first century is crucial. This is typically viewed as a supply-side development issue due to destitution and the dearth of alternative employment opportunities.